Awareness and Implementation of Total Quality Management: The case of Enterprises in Danang City - Nguyen, Thi Bich Thuy (University of Economics Ho Chi Minh City, 2023)
Implementation of quality management in accordance with advanced quality management models, especially the Total Quality Management (TQM) approach, is crucial to the outcome quality of organizations, customer satisfaction, organizational competitive advantages, and financial performance in the present integrating environment. This study aims to construct measures to assess the awareness and implementation situation of TQM among the enterprises in Danang city. The results show that despite a high level of quality awareness by the managers, the TQM implementation is still limited among the surveyed businesses.